2021
DOI: 10.3389/fnhum.2021.673003
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Changes With Rehabilitation in Children With Developmental Coordination Disorder: A Randomized Controlled Trial

Abstract: Background and Objectives: Children with developmental coordination disorder (DCD) have difficulty learning motor skills, which can affect their participation in activities of daily living and psychosocial well-being. Over 50% of children with DCD also have attention deficit hyperactivity disorder (ADHD), which further exacerbates their motor problems and impact on quality of life. A rehabilitation approach known as Cognitive Orientation to Occupational Performance uses problem-solving strategies to help child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 141 publications
(212 reference statements)
3
8
0
Order By: Relevance
“…The divergence in maturational pathways of the CST between those with ADHD + MI and ADHD supports recent arguments that motor difficulties observed in ADHD reflect a distinct symptom cluster rather than a core phenotypic characteristic of ADHD (Farran et al, 2020;Goulardins et al, 2015;Lee et al, 2021). This is inkeeping with a small existing body of literature that suggests distinct Zwicker, 2021). This study highlights that the CST may not be as susceptible to experientially driven plasticity in those with combined ADHD + MI relative to those with just one of the two disorders in isolation.…”
Section: Discussionsupporting
confidence: 79%
“…The divergence in maturational pathways of the CST between those with ADHD + MI and ADHD supports recent arguments that motor difficulties observed in ADHD reflect a distinct symptom cluster rather than a core phenotypic characteristic of ADHD (Farran et al, 2020;Goulardins et al, 2015;Lee et al, 2021). This is inkeeping with a small existing body of literature that suggests distinct Zwicker, 2021). This study highlights that the CST may not be as susceptible to experientially driven plasticity in those with combined ADHD + MI relative to those with just one of the two disorders in isolation.…”
Section: Discussionsupporting
confidence: 79%
“…The attendant gains in skill, however small, have a reinforcing effect on the motivation of children and their willingness to persist in training. Interestingly, recent evidence shows that gains in motor performance following a Cognitive Orientation to Occupational Performance (CO-OP) intervention are accompanied by a sustained increase in white matter microstructure and functional connectivity between brain networks associated with emotion regulation, action inhibition, and attention for those with DCD (but not DCD+ADHD) (Izadi-Najafabadi and Zwicker, 2021 ; Izadi-Najafabadi et al, 2021 ). Together, the available evidence provides encouraging support for science-led intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Increased screen exposure time has previously been associated with lower microstructural integrity of brain white matter tracts in preschool-aged children ( 45 ). Children with DCD also showed significant brain differences in motor and sensorimotor white matter pathways when compared with controls ( 46 , 47 ). Furthermore, evidence suggested that higher screen exposure is independently associated with lower serum Brain-derived neurotrophic factor (BDNF) levels ( 48 ).…”
Section: Discussionmentioning
confidence: 99%